Fabrication and electroluminescence properties of alloyed CdSxSe1−x quantum dots-based LEDs. (21st January 2022) - Nguyen, Huu Tuan; Chen, Shutang; Duong, Anh Tuan; Lee, Soonil
Abstract: We report on the facile synthesis of alloyed CdS x Se1− x quantum dots (QDs) via a one-pot method using the simultaneous injection of Se and S source into a solution of the Cd precursor dissolved in a coordinating mixture of hexadecylamine and trioctylphosphine, during which the formation of CdS x Se1− x nanocrystals was controlled by growth time at a temperature of 260 °C. In particular, the emission peak and full width at half maximum of the photoluminescence (PL) of alloyed CdS x Se1− x QDs were tunable in the range of 588–604 nm and 36–38 nm, respectively, with a PL quantum yield of up to 55% by a reaction time of 60 min. Importantly, the structural advantage of alloyed CdS x Se1− x QDs-based light emitting devices have been fabricated and their electroluminescence properties characterized. A good performance device with a maximum luminance and luminous efficiency of 761 cd m −2 and 0.82 cd A −1, respectively, was obtained.